Identifikasi Miskonsepsi Materi Sistem Tata Surya Menggunakan Three-Tier Diagnostic Test dengan Certainty Response Index - Leoniza, Malfa Betries Tien; Styawati, Riski; Umami, Salsa Rahmatul; Thohir, M. Anas; Utama, Candra (PendIPA Journal of Science Education, 2025)
Misconceptions are a phenomenon that is often experienced in the learning process, that is important to identify so it doesn't occur continuously. However, in the research that has been conducted regarding misconceptions about the solar system, there has been no research conducted in elementary schools. In addition, the research that has been conducted is only based on interviews without diagnostic tests. This study aimed to identify the level of misconceptions about the solar system material of grade VI students at an elementary school in Trenggalek regency. This research was qualitative research using a three-tier Certainly Response Index. The first tier was conceptual understanding, the second tier was the reason for choosing an answer, the third tier was the student's level of confidence in the previous answer. The results of this study indicated that in general 56.875% of students experience misconceptions. If reviewed from each concept, 65.63% of students experienced misconceptions in solar system concepts, 51.65% of students experienced misconceptions in earth's rotation and revolution concepts, while 50% students experienced misconceptions in eclipse concepts. Meanwhile, if reviewed from each question, misconceptions occur in question number 10 about determining the characteristics of the sun with a percentage of 81.25% with a high misconception category. The results of this identification are expected to be used as a reference for designing learning materials on the solar system.